2017
DOI: 10.1007/s10570-017-1549-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural factors affecting 13C NMR chemical shifts of cellulose: a computational study

Abstract: The doublet C4 peaks at * 85 and * 89 ppm in solid-state 13 C NMR spectra of native cellulose have been attributed to signals of C4 atoms on the surface (solvent-exposed) and in the interior of microfibrils, designated as sC4 and iC4, respectively. The relative intensity ratios of sC4 and iC4 observed in NMR spectra of cellulose have been used to estimate the degree of crystallinity of cellulose and the number of glucan chains in cellulose microfibrils. However, the molecular structures of cellulose responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 52 publications
1
47
0
1
Order By: Relevance
“…Figure 2a shows the 13 C CP MAS spectrum of the pulp with the assignment proposed based on the previous literature, supported by both experimental data [46] and computational study. [47] The F I G U R E 5 13 C cross polarisation spectra of the DuPont AFFINISOL™ hydroxypropylmethylcellulose acetyl succinate series at (a) L grade, (b) M grade, and (c) H grade of acetyl/succinoyl ratio. The simulated spectrum (dashed black) and the spectral deconvolution (grey line) are given for each spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2a shows the 13 C CP MAS spectrum of the pulp with the assignment proposed based on the previous literature, supported by both experimental data [46] and computational study. [47] The F I G U R E 5 13 C cross polarisation spectra of the DuPont AFFINISOL™ hydroxypropylmethylcellulose acetyl succinate series at (a) L grade, (b) M grade, and (c) H grade of acetyl/succinoyl ratio. The simulated spectrum (dashed black) and the spectral deconvolution (grey line) are given for each spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed assignments are based on the previous literature. [46,47] The simulated spectrum (dashed black) and the spectral deconvolution (grey line) are also given for the CP spectrum. The red dotted line in (b) marks the zero intensity signal T A B L E 1 Degree of substitution (DS) of acetate (A) and succinate (S) moieties in the various Hydroxypropylmethylcellulose-AS polymers studied here as a function of manufacturers and grade.…”
Section: Synthesis Of Hpmc-amentioning
confidence: 99%
“…Based on a computational study, it has been reported that the conformation of the exocyclic groups at C6 significantly influences the C4 peak separation, and the signal at approximately 89 ppm, corresponding to the crystalline C4 carbon, is dominated by the tg conformation [31]. Figure 4 shows the relationship between the C4-based CI value and the C6-based tg ratio of samples with different crystal sizes.…”
Section: Relationship Between C4-based CI Value and C6-based Tg Ratiomentioning
confidence: 99%
“…This result demonstrates that the change in the C4 crystalline signal is strongly affected by the tg conformation. The slight difference from 1.0 in the slope leads to the interpretation that the glycosidic linkage is partly restricted even when the C6 hydroxy groups sit in the noncrystalline gt conformation [31].…”
Section: Relationship Between C4-based CI Value and C6-based Tg Ratiomentioning
confidence: 99%
“…The regions between 80 and 92 ppm and 60 and 67 ppm are assigned to C4 and C6 carbons in the glucose unit . The chemical shifts of C6 and C4 represent different torsion angles of the C5−C6 bond, which are good indicators of structural changes . The regions between 87 and 92 ppm and 64 and 67 ppm, attributed to crystalline interior cellulose chains, nearly completely disappear after ball milling, indicative of conversion of interior chains to external ones with ball milling.…”
Section: Resultsmentioning
confidence: 99%